Association of antibodies to benzo[a]pyrene, estradiol and progesterone with gene polymorphisms of cytokines in postmenopausal women - E. G. Polenok; L. A. Gordeeva; S. A. Mun; E. N. Voronina; G. I. Kolpinsky; V. A. Lutsenko; E. V. Brezhneva; M. V. Kostyanko; I. A. Vafin; A. A. Glushkov (Медицинская иммунология)
Previous studies reported some associations between IgA and IgG antibodies specific to benzo[a] pyrene (Bp), estradiol (Es) and progesterone (Pg), and breast cancer (BC) in postmenopausal women. Likewise, the individual ratios of these antibodies (IgA-Bp/IgA-Pg, IgG-Bp/IgG-Pg, IgG-Es/IgG-Pg, IgG-Es/IgG-Pg) were associated with BC. It was suggested that development of antibodies to chemical carcinogens and steroid hormones was determined by functional polymorphisms of cytokine genes. The purpose of this study was to identify the suggested associations of antibodies to Bp, Es, Pg, and their individual ratios to the following gene polymorphisms: IL1RN (rs4251961), IL1B (rs16944), IL6 (rs1800795, rs1800796, rs1554606), IL8 (rs4073), TNFA (rs1800629) and CD40 (rs6074022) detected in postmenopausal healthy women and BC patients.The serum IgA and IgG antibodies specific to Bp, Es and Pg were studied in 470 healthy women and 995 BC patients by non-competitive solid phase immunoassay. The conjugates of Bp, Es, Pg with bovine serum albumin were used as adsorbed antigen. The goat antibodies against human IgA or IgG conjugated with horseradish peroxidase were used for the detection of bound hapten-specific antibodies. Cytokine gene polymorphisms were analyzed by the real-time PCR.Associations between the studied antibodies and their ratios with the gene polymorphisms in IL1RN (rs4251961), IL6 (rs1800795), TNFA (rs1800629) and CD40 (rs6074022) were found in healthy women. Higher individual ratios of IgA-Bp/IgA-Pg (p = 0.0001), IgG-Bp/IgG-Pg (p < 0.0001), IgG-Es/IgG-Pg (p = 0.0003) were associated with the allele C gene IL1RN. The higher IgG-Es levels were more common in the persons with allele G gene IL6 (p = 0.007), and with C allele of CD40 gene (p = 0.005). The high IgA-Pg levels were associated with A allele gene of TNFA (p = 0.008). Associations of antibodies were found only with genes polymorphisms in CD40 (rs6074022) in BC patients. Higher IgG-Es levels were more common in persons with allele T gene CD40 (p = 0.007).In conclusion, we revealed the participation of cytokines in immune regulation of antibody genesis for environmental chemical carcinogens and endogenous steroid hormones in healthy women and BC patients. The future investigations of antibodies specific to Bp, Es and Pg combined with the analysis genes polymorphisms in cytokines will be useful for detection of the individual hormone-dependent cancer risks in humans.